An artificial neural networks approach to product cost estimation. The case study for electric motor - Leszczyński, Zbigniew; Jasiński, Tomasz (Sztuczne sieci neuronowe w prognozowaniu kosztów produktu. Studium przypadku dla silnika elektrycznego, 2018)
The aim of this paper is to present, in theoretical and application terms, artificial neural networks (ANNs) as a method of estimating the product cost. The first part of the article reviews the methods used to estimate the product cost. The basic approaches to the problem of product cost estimation, presented by various authors, were described. In the second part an empirical study using artificial neural networks was conducted. Two research methods were used in this paper: literature analysis and empirical research carried out in the form of an extensive case study. The test object is a new generation induction motor. The main research problem of the article is the modelling of artificial neural networks for the estimation process of product costs with advanced production technology. The test procedures focus on the application aspects. The conclusions discuss the usefulness and advantages of using ANN models in estimating the costs of products
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 1 (47), s. 72-84
Keywords: cost estimation model; artifical neural networks; product cost; prognozowanie kosztów; sztuczne sieci neuronowe; koszt produktu